Correction: Actuated 3D microgels for single cell mechanobiology. Issue 18 (17th August 2022) - Özkale, Berna; Lou, Junzhe; Özelçi, Ece; Elosegui-Artola, Alberto; Tringides, Christina M.; Mao, Angelo S.; Sakar, Mahmut Selman; Mooney, David J.
Abstract : Correction for 'Actuated 3D microgels for single cell mechanobiology' by Berna Özkale et al., Lab Chip, 2022, 22, 1962–1970, ; https://doi.org/10.1039/D2LC00203E .